Modeling human influenza infection in the laboratory - Radigan KA; Misharin AV; Chi M; Scott Budinger GR (Infection and Drug Resistance, 2015)
Kathryn A Radigan,1 Alexander V Misharin,2 Monica Chi,1 GR Scott Budinger11Division of Pulmonary and Critical Care Medicine, 2Division of Rheumatology, Northwestern University Feinberg School of Medicine, Chicago, IL, USAAbstract: Influenza is the leading cause of death from an infectious cause. Because of its clinical importance, many investigators use animal models to understand the biologic mechanisms of influenza A virus replication, the immune response to the virus, and the efficacy of novel therapies. This review will focus on the biosafety, biosecurity, and ethical concerns that must be considered in pursuing influenza research, in addition to focusing on the two animal models – mice and ferrets – most frequently used by researchers as models of human influenza infection.Keywords: mice, ferret, influenza, animal model, biosafety